Migratory patterns and estimated population size of pygmy blue whales (Balaenoptera musculus brevicauda) traversing the Western Australian coast based on passive acoustics. - McCauley, Robert; Jenner, Curt (International Whaling Commission, 2010)
Passive acoustic data sets along the Western Australian coast have revealed annual southnorth migrations of pygmy blue whales. At the latitude of Exmouth (21o 30’ S) a sharp southerly travelling pulse of pygmy blue whales is experienced each year over October to late December, while a more protracted northerly pulse of returning animals is detected over the following April to August. It is believed the south bound pulse of animals passing Exmouth are steadily migrating. The passive acoustic detections of pygmy blue whales off Exmouth have been converted to instantaneous counts of the number of individual whales calling. By assuming a range of proportions of animals calling of from 8.5-20% of total pygmy blue whales in the area, the number of individual whales calling has been converted to estimates of the number of whales in the noise logger listening area, at 15 minute increments across the southerly migratory pulse. This curve was integrated across the migratory season. The listening range of the noise logger and the whale swim speed along a known route were used to give whale residency time in the noise logger listening area. The integrated curve of whale days was divided by the residency time to give an estimate of 662-1559 pygmy blue whales passing the noise logger site during the 2004 southerly migratory pulse down the Western Australian coast. We know pygmy blue whales reside along the east Australian coast and in the southern Indian Ocean, thus the population estimate for Western Australia is a portion of the larger Indian and western Pacific pygmy blue whale population.